Examining the sustainability of second-hand clothing supply chain - Jääskeläinen, Milvi (My University, 2024)
The sustainability of clothing industry is a well known fact, but second-hand clothing industry’s sustainability is not common knowledge. However, second-hand clothing is increasingly popular among consumers and hence the size of the market has grown making the supply chains fragmented and internationally scattered to the Global North and the Global South. This thesis will cover the research problem to outline the second-hand clothing supply chain in order of the processes aiming to find the main sustainability problems. In addition, this thesis will cover the consumer behavior’s effect on the second-hand clothing supply chain’s sustainability. The literature shows there to be several environmental and social sustainability problems throughout the supply chain’s processes. Major sustainability problem in both the Global North and the Global South is clothing waste leaking from the supply chain’s processes like disposal, sorting, consumer’s disposal behavior and exporting. The waste leaks create both environmental sustainability questions as social sustainability question hence the clothing waste imported to the Global South is mainly from the Global North. In addition, consumers have a greate impact on the amount and quality of the second-hand clothing and clothing waste through starting the supply chain when disposing clothing to collectors. However, the change in consumer behavior towards consuming second-hand clothing has surfaced many sustainability questions about the true sustainability of the market. Main environmental sustainability problem is the rising characteristic of fast fashion consumption in second-hand clothing consumption. Furthermore, the main social sustainability problem is the increase in prices through increasing demand of second-hand clothing creating a question about inequality between wealth branches.

Vaateteollisuuden kestämättömyys on hyvin tiedetty fakta, kun taas käytettyjen vaatteiden teollisuuden kestävyys ei ole yleisesti tiedossa. Käytetyt vaatteet ovat jatkuvasti lisää suosiota saavuttava tuote, ja markkinan kasvu aiheuttaa toimitusketjun hajautumisen kansainvälisesti globaaliin pohjoiseen ja globaaliin etelään. Tämän tutkielman tutkimusongelmana on tarkastella käytettyjen vaatteiden toimitusketjun pääpiirteet käymällä läpi ketjun prosessit. Tavoitteena tutkielmalle on löytää merkittävimmät kestävyysongelmat toimitusketjun eri prosesseista. Lisäksi tutkielman toisena tutkimusongelmana on arvioida kuluttajakäyttäytymisen vaikutusta käytettyjen vaatteiden toimitusketjun kestävyyteen. Kirjallisuus osoittaa, että käytettyjen vaatteiden toimitusketjun prosesseissa ilmenee useampia ympäristön ja sosiaalisen kestävyyden ongelmia. Merkittävä ongelma kestävyydessä on vaatejäte, jota vuotaa toimitusketjun eri prosesseissa, kuten vaatteiden hävittämisessä, lajittelussa, kuluttajien vaatteiden hävityksessä sekä vaatteiden viennissä. Tämä ongelma ilmenee niin globaalissa etelässä kuin globaalissa pohjoisessa. Vaatejätteen vuodot aiheuttavat niin ympäristön kuin sosiaalisen kestävyyden ongelmia, sillä globaaliin etelään viety vaatejäte on pääasiassa peräisin globaalista pohjoisesta. Kuluttajat aloittavat koko käytettyjen vaatteiden toimitusketjun luovuttaessa vaatteensa kerääjälle. Näin kuluttajilla on merkittävä vaikutus käytettyjen vaatteiden ja vaatejätteen laatuun. Kuluttajakäyttäytymisen muutos käytettyjen vaatteiden kuluttamisen suuntaan on kuitenkin nostanut esiin monia kestävyyteen liittyviä ongelmia. Merkittävä ympäristön kestävyyden ongelma nousee esiin käytettyjen vaatteiden kuluttamisen muuttuessa kohti pikamuotivaatteiden kulutuksen piirteitä. Merkittävä sosiaalisen kestävyyden ongelma puolestaan on käytettyjen vaatteiden hinnan kasvu kasvaneen kysynnän vaikutuksesta. Tämä herättää huolen epätasa-arvosta tuloluokkien välillä.
Keywords: Circular Economy, Sustainability, Supply Chains, Consumer Behaviour, Global North, Global South, Second-Hand Clothing